Demographic Diversity in the Boardroom: Mediators of the Board Diversity–Firm Performance Relationship - Miller, Toyah; Del Carmen Triana, María (Journal of Management Studies, 2009)
abstract Whereas the majority of research on board diversity explores the direct relationship between racial and gender diversity and firm performance, this paper investigates mediators that explain how board diversity is related to firm performance. Grounded in signalling theory and the behavioural theory of the firm, we suggest that this relationship operates through two mediators: firm reputation and innovation. In a sample of Fortune 500 firms, we find a positive relationship between board racial diversity and both firm reputation and innovation. We find that reputation and innovation both partially mediate the relationship between board racial diversity and firm performance. In addition, we find a positive relationship between board gender diversity and innovation.